2019
DOI: 10.14712/23361964.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of arbuscular mycorrhizal fungi and Pseudomonas fluorescens on growth, physiological parameters and essential oil content in Ocimum basilicum L.

Abstract: A pot experiment was performed to see the interactive potential of Glomus mosseae and Acaulospora laevis alone or in combination with Pseudomonas fluorescens on Ocimum basilicum L. under glass house conditions. Various morphological and physiological parameters were measured after 120 days. Although, all co-inoculation treatments showed beneficial effects but G. mosseae is found to be the most compatible strain found in the rhizosphere of basil plant. G. mosseae alone or in combination with other bioinoculants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Also, Nafady et al (2018) stated that AMF symbiosis can provide mineral nutrients for faba bean plant growth and improved the structure of the soil. Moreover, Jangra et al (2019) on Ocimum basilicum L. demonstrated that the co-inoculation of Pseudomonas fluorescens with AMF increased nutrient absorption especially phosphorus. Also, Khatun (2020) indicated that the P content of leaf tissue remains higher in AMF Coleus plants as compared to non-mycorrhizal ones and there was an increase in the amount of phosphorus with increase in age of the plant.…”
Section: Impact Of F Mosseae Chm and Fym Rates And Their Interaction ...mentioning
confidence: 99%
“…Also, Nafady et al (2018) stated that AMF symbiosis can provide mineral nutrients for faba bean plant growth and improved the structure of the soil. Moreover, Jangra et al (2019) on Ocimum basilicum L. demonstrated that the co-inoculation of Pseudomonas fluorescens with AMF increased nutrient absorption especially phosphorus. Also, Khatun (2020) indicated that the P content of leaf tissue remains higher in AMF Coleus plants as compared to non-mycorrhizal ones and there was an increase in the amount of phosphorus with increase in age of the plant.…”
Section: Impact Of F Mosseae Chm and Fym Rates And Their Interaction ...mentioning
confidence: 99%
“…Filamentous compost fungi such as Aspergillus and Mucor may play a fundamental role [51,52] as conduits for efficient colonization of roots and soil habitats or the access to soil nutrients [7,18]. For instance, co-inoculation of biocontrol bacteria Pseudomonas fluorescens with arbuscular mycorrhizal Glomus mosseae demonstrated that P. fluorescens enabled better mycorrhizal colonization of roots of basil (Ocimum basilicum L.) [60].…”
Section: Isolation Of Fungi and Associated Migrator Bacteriamentioning
confidence: 99%